2016
DOI: 10.18632/oncotarget.8582
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the diagnostic and prognostic value of circulating cathepsin S in gastric cancer

Abstract: To evaluate whether serum Cathepsin S (Cat S) could serve as a biomarker for the diagnosis and prognosis of gastric cancer (GC), Enzyme-linked immuno sorbent assay (ELISA) was used to detect serum Cat S in 496 participants including healthy controls and patients with benign gastric diseases, gastric cancer, esophageal cancer, liver cancer, colorectal cancer, nasopharyngeal cancer and lung cancer. The levels of serum Cat S were significantly increased in cancer patients, especially in GC patients. The qRT-PCR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 43 publications
2
34
0
1
Order By: Relevance
“…Cat S is of paramount importance in cell migration and invasion. It has been observed that silencing Cat S by specific siRNAs leads to inhibition of GC cell invasion (31). The same was observed for other cancer cells, such as hepatocellular carcinoma, lung adenocarcinoma, and skin melanoma cells.…”
Section: Cathepsin S and Carcinogenesissupporting
confidence: 56%
“…Cat S is of paramount importance in cell migration and invasion. It has been observed that silencing Cat S by specific siRNAs leads to inhibition of GC cell invasion (31). The same was observed for other cancer cells, such as hepatocellular carcinoma, lung adenocarcinoma, and skin melanoma cells.…”
Section: Cathepsin S and Carcinogenesissupporting
confidence: 56%
“…Current methods for diagnosis and monitoring of GC include invasive tests, such as endoscopy and biopsy; however, such tests are limited due to their high cost and invasiveness (3). Esophagogastroduodenoscopy, one of the most reliable methods for diagnosis of GC, is broadly used in China, South Korea and Japan, where the incidence rates of GC are high, while the effectiveness and feasibility of gastroscopy is questionable for countries with low GC incidence rates (2).…”
Section: Introductionmentioning
confidence: 99%
“…20,21 However, most of the proteases are also found in high concentration in the serum of patients with tumors. For example, a number of studies reported higher circulating levels and enzyme activities of MMPs (2, 7 or 9) and CATs (B, L and K) in various tumors, [22][23][24] suggesting the prodrugs or probes have the potential risk of degradation by these proteases in human blood. Recently, accumulated evidence has shown that there is an increasing interest in FAPα-activated drugs and probes, which have been explored in the diagnosis and treatment of various solid tumors.…”
Section: Discussionmentioning
confidence: 99%